MENGENALKAN MATEMATIKA PADA ANAK SEJAK USIA DINI DI DESA DURUNG BEDUG - Lestariningsih Lestariningsih (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2018)
This community service program about introducing mathematics to children since early age in Durung Bedug Village aims to overcome the problems of most parents who have difficulty in introducing mathematics to children from an early age. This activity is done in the form of seminar and done in 3 stages. In the first stage, observation is carried out on the program objectives to determine the method of delivering the seminar in accordance with the target condition and situation. In addition, coordination with village officials for licensing issues as well as preparing various things related to activities. In the second stage of the implementation phase, we explain the materials about introducing mathematics to children from an early age. At the end of the stage, we conducted further activities in the form of consultation or further guidance for parents who want to deepen the insights about ways or strategies in introducing mathematics to children from an early age. After all activities carried out the proposer prepares the activity report. Community service activities are done through the description that has been presented; this activity received a good response from the residents in Durung Bedug Village. They can know about ways or strategies in introducing mathematics to children from an early age and can motivate children to enjoy learning and reduce the difficulties children experience in learning math later in life..